2007
DOI: 10.1002/joc.1645
|View full text |Cite
|
Sign up to set email alerts
|

Climate change prediction over complex areas: spatial variability of uncertainties and predictions over the Pyrenees from a set of regional climate models

Abstract: ABSTRACT:We used a set of six regional climate models (RCMs) from PRUDENCE project to analyse the uncertainties and direction and magnitude of the expected changes on precipitation and temperature (B2 and A2 scenarios) for the end of the 21st century in the Pyrenees, south of Europe. There have been few studies of climate change effects on this mountain range, though there can be noticeable impacts on the economy and ecology of the region and the surrounding lowlands. The analysis of the accuracy of the RCMs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 53 publications
(51 reference statements)
2
90
0
7
Order By: Relevance
“…Selection of this model was based on its ability to reproduce temperature and precipitation over the Pyrenees and the center of the Ebro valley. Moreover, it was compared with a set of regional climate model projections from the PRUDENCE dataset, as this model is representative of the mean sign and magnitude of the multimodel ensemble average (López-Moreno et al, 2008a). Figure 2 shows the trend of annual and seasonal precipitation across the Ebro basin during the studied period .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Selection of this model was based on its ability to reproduce temperature and precipitation over the Pyrenees and the center of the Ebro valley. Moreover, it was compared with a set of regional climate model projections from the PRUDENCE dataset, as this model is representative of the mean sign and magnitude of the multimodel ensemble average (López-Moreno et al, 2008a). Figure 2 shows the trend of annual and seasonal precipitation across the Ebro basin during the studied period .…”
Section: Methodsmentioning
confidence: 99%
“…Large variations in precipitation and evapotranspiration occur throughout the region (Ninyerola et al, 2005;Vicente-Serrano et al, 2007), and annual precipitation varies from 307 to 2451 mm yr −1 . Most of the precipitation falls in autumn and spring, although in some areas the maximum precipitation occurs in winter and summer (López-Moreno et al, 2008b). Average annual temperature varies from 0.8 to 16.2 • C.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…1), which imprinted a sharp horizontal change in ecosystem composition. The two macro-regions are characterised by major climatic differences in water availability and temperature (López-Moreno et al, 2008), with Mediterranean climate being generally warmer, drier and comparatively of larger inter-seasonal variability than the Atlantic climate. This means potential tipping points in alpine lake ecosystems due to climate change effects (particularly through sharp changes in water temperature and dynamics; Khamis et al, 2014) is likely to happen faster across horizontal than vertical gradients in biogeographical boundary regions such as this one, with potentially unexpected effects.…”
Section: Large Geographical Gradientsmentioning
confidence: 99%
“…Changes in snow and ice are one of the easiest impacts of climate change to be perceived since they respond rapidly to slight variations in precipitation and temperature (López-Moreno et al, 2008;Nesje and Dahl, 2000). Many studies have reported a decrease in snow thickness and duration in many mountain areas in the world.…”
Section: Introductionmentioning
confidence: 99%